Low Counts of Faecalibacterium prausnitzii in Colitis Microbiota - Sokol, H.; Seksik, P.; Furet, J. P.; Firmesse, O.; Nion-Larmurier, I.; Beaugerie, L.; Cosnes, J.; Corthier, G.; Marteau, P.; Doré, J. (Inflammatory bowel diseases, 2009)
The intestinal microbiota is suspected to play a role in colitis and particularly in inflammatory bowel disease (IBD) pathogenesis. The aim was to compare the fecal microbiota composition of patients with colitis to that of healthy subjects (HS).Methodsfecal samples from 22 active Crohn's disease (A-CD) patients, 10 CD patients in remission (R-CD), 13 active ulcerative colitis (A-UC) patients, 4 UC patients in remission (R-UC), 8 infectious colitis (IC) patients, and 27 HS were analyzed by quantitative real-time polymerase chain reaction (PCR) targeting the 16S rRNA gene. Bacterial counts were transformed to logarithms (Log10 CFU) for statistical analysis.ResultsBacteria of the phylum Firmicutes (Clostridium leptum and Clostridium coccoides groups) were less represented in A-IBD patients (9.7; P = 0.004) and IC (9.4; P = 0.02), compared to HS (10.8). Faecalibacterium prausnitzii species (a major representative of the C. leptum group) had lower counts in A-IBD and IC patients compared to HS (8.8 and 8.3 versus 10.4; P = 0.0004 and P = 0.003). The Firmicutes/Bacteroidetes ratio was lower in A-IBD (1.3; P = 0.0001) and IC patients (0.4; P = 0.002). Compared to HS, Bifidobacteria were less represented in A-IBD and IC (7.9 and 7.7 versus 9.2; P = 0.001 and P = 0.01).ConclusionsThe fecal microbiota of patients with IBD differs from that of HS. The phylum Firmicutes and particularly the species F. prausnitzii, are underrepresented in A-IBD patients as well as in IC patients. These bacteria could be crucial to gut homeostasis since lower counts of F. prausnitzii are consistently associated with a reduced protection of the gut mucosa.